EXTRATERRITORIAL APPLICABILITY OF INDONESIA BUSINESS COMPETITION LAW AS AN EFFORTS DEALING ASEAN SINGLE MARKET - Kurnia Toha (Faculty of Law, Universitas Jenderal Soedirman, 2015)
General legal principle, a legislation of a country applies only for acts committed in the territories concerned. This principle, to the field of competition has not felt right, because economic activity not only occur between the businesses in the country, but also with businesses that are abroad. Therefore, there is a need for competition law of a country can be enforced in ekstraterritorial. The problem, Law Number 5 of 1999 adheres to the principle of territoriality does not adhere to the principle of extraterritoriality. In this study, the method used is the literature research. The study found that the principle of extraterritoriality adopted by various developed countries and some countries in Asia. The study also found that there is an urgent need that the Indonesian competition law applies to companies abroad, especially in 2015 will force the ASEAN single market.Keywords : Ekstraterritorial , Competition Law , Business Actors